Factors Related to Severity of Diabetic Foot Ulcer: A Systematic Review - Pratiwi, Niken; Barry, Barry (The Indonesian Journal of General Medicine, 2024)
Background: Diabetes mellitus (DM) has become a pressing global health concern, with the number of cases escalating significantly over the past few decades. Diabetic foot ulcers (DFUs), among the complications of DM, present a substantial burden, with prevalence rates ranging from 4 to 10% and severe cases associated with heightened mortality rates. This study aims to consolidate research findings on the factors influencing DFU severity to inform preventive strategies and improve patient care. Methods: This systematic review focused on full-text English literature published between 2014 and 2024 using the PRISMA 2020 guidelines. The literature was compiled using PubMed, ScienceDirect, and SagePub, among other online venues. Result: Five publications were found to be directly related to our ongoing systematic examination after a rigorous three-level screening approach. Subsequently, a comprehensive analysis of the complete text was conducted, and additional scrutiny was given to these articles. Conclusion: Diabetic foot ulcer (DFU) is a serious complication of diabetes, influenced by various factors, including lifestyle and self-care practices. Educating patients on proper foot hygiene and care, along with comprehensive training for healthcare providers, can mitigate DFU severity.